The Antimicrobial Effects of Coffee and By-Products and Their Potential Applications in Healthcare and Agricultural Sectors: A State-of-Art Review - Rosa Castro-Díaz; Norma Patricia Silva-Beltrán; Nohemi Gámez-Meza; Kadiya Calderón (Microorganisms)
Coffee is one of the most consumed beverages around the world. Its production is dominated by the species Coffea arabica and Coffea canephora. However, the coffee elaboration process leads to generating a significant amount of waste, which arises in various stages of coffee bean processing and is rich in natural bioactive compounds such as phenolic compounds and alkaloids. Particularly, chlorogenic and caffeic acids have a high antimicrobial potential and have been demonstrated to be effective against bacteria and viruses of healthcare and food relevance, including multi-resistant pathogens. However, the production and accumulation of coffee waste have a negative environmental impact since they can contaminate the surrounding environment due to the presence of organic molecules such as caffeine and tannins. In this context, exploiting natural resources as a source of compounds with the antimicrobial potential of, for example, the bioactive compounds obtained from coffee, has been evaluated in previous works. This review aims to summarize the current knowledge on the antimicrobial properties of coffee and its by-products and their potential application in the healthcare sector and disease control in agricultural crops, with particular emphasis on improving sustainability and efficiency in agriculture through making use of waste, which carries high importance in today’s society.